Resolution of cellular compartments involved in membrane potential changes accompanying IgE-mediated degranulation of rat basophilic leukemia cells. - Sagi-Eisenberg, R (1984)
The overall membrane potential of rat basophilic leukemia cells (RBL-2H3) calculated from the transmembrane distribution of the lipophilic, tritium-labelled cation tetraphenyl-phosphonium [( 3H]TPP+) was resolved into its mitochondrial and plasma membrane potential components. Using the mitochondrial uncoupler carbonylcyanide-p-trifluormethoxyphenyl hydrazone (FCCP) which collapses the mitochondrial potential, it was shown that about one third of the overall potential resulted from the mitochondrial contribution. Degranulation of the RBL cells induced by two different IgE-cross-linking agents (specific antigen and anti-IgE antibodies), was accompanied by, and well correlated with, a decrease in the overall potential. However, evaluation of the source of these observed potential changes revealed that the FCCP-insensitive fraction of the overall potential, delta psi P, (representing the plasma membrane potential), was not affected. In contrast, the FCCP-sensitive component due to the mitochondrial potential decreased when receptor cross-linking increased. Thus, the observed decrease in the overall potential is most probably a secondary event in the sequence leading from stimulus to secretion. Indeed, exposure of the RBL cells either to a high external concentration of K+ ions or to a high amount of external TPP+, both causing depolarization, failed to trigger degranulation. It is suggested that the apparent decrease in the measured overall potential is a reflection of the mitochondrial membrane depolarization. The latter is most probably caused by mitochondrial Ca2+ uptake initiated by the increase in the intracellular concentration of Ca2+ which follows cells activation.